A ética e a política no pensamento de Nicolau Maquiavel - Adriano Euripides Medeiros Martins (2002)
We have sought to maintain the thesis which opposes the traditional view that conceives Maquiavel as an immoral. According to our standpoint an another Maquiavel emerges, endowed with an ethical and political ideal, that is, the Republican State, where is possible to effectively achieve "the common well". That is why we point out the existence of an ethical project the republic, although this ideal does not include the same ways of the traditional ethic since, according to Maquiavel, ethics is subordinated to politics. It is liberty's political maintenance.